Postmortem Findings in Italian Patients With COVID-19: A Descriptive Full Autopsy Study of Cases With and Without Comorbidities. (11th September 2020) - Falasca, Laura; Nardacci, Roberta; Colombo, Daniele; Lalle, Eleonora; Di Caro, Antonino; Nicastri, Emanuele; Antinori, Andrea; Petrosillo, Nicola; Marchioni, Luisa; Biava, Gianluigi; D'Offizi, Gianpiero; Palmieri, Fabrizio; et al.
Abstract: Background: Descriptions of the pathological features of coronavirus disease-2019 (COVID-19) caused by the novel zoonotic pathogen severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) emanate from tissue biopsies, case reports, and small postmortem studies restricted to the lung and specific organs. Whole-body autopsy studies of COVID-19 patients have been sparse. Methods: To further define the pathology caused by SARS-CoV-2 across all body organs, we performed autopsies on 22 patients with COVID-19 (18 with comorbidities and 4 without comorbidities) who died at the National Institute for Infectious Diseases Lazzaro Spallanzani-IRCCS Hospital, Rome, Italy. Tissues from the lung, heart, liver, kidney, spleen, and bone marrow (but not the brain) were examined. Only lung tissues were subject to transmission electron microscopy. Results: COVID-19 caused multisystem pathology. Pulmonary and cardiovascular involvement were dominant pathological features. Extrapulmonary manifestations included hepatic, kidney, splenic, and bone marrow involvement, and microvascular injury and thrombosis were also detected. These findings were similar in patients with or without preexisting medical comorbidities. Conclusions: SARS-CoV-2 infection causes multisystem disease and significant pathology in most organs in patients with and without comorbidities. Abstract : Autopsy findings in patients with COVID-19 showed deaths were due to cardiorespiratory failure, predominantly caused by acute lung injury, microvascular damage, and thrombosis. COVID-19 causes multisystem disease and significant pathology in most organs in patients with and without comorbidities.